Effect of a reused insulin needle remaining in a patient's body - Yong‐jie Qiao; Yu Xin‐yuan; Rui‐ling Xu; Xiao‐yang Song; Shuo Ye; Ping Zhen; Sheng‐hu Zhou; Hao‐qiang Zhang (Journal of Diabetes Investigation, 2023)
Abstract Diabetes is one of the most common chronic diseases at present, and insulin pen injection therapy plays an important role in the treatment of diabetes. However, the majority of patients might reuse disposable insulin pen needles for various reasons, which leads to related complications. As far as we know, this article is the first to describe a patient whose needle remained in the right upper limb while reusing a disposable insulin injection needle for subcutaneous insulin injection with the non‐dominant hand. The patient went to the doctor 1 week later. The needle moved from the lateral area of the proximal upper arm (the injection site) to the posterolateral area of the distal upper arm. The needle was then successfully removed by surgery. The reuse of disposable insulin pen needles might lead to serious complications. It is suggested to strengthen the education of people living with diabetes to help them use insulin pen needles safely.